Bacterial hemagglutination by Neisseria gonorrhoeae. - Koransky, J R (1975)
Direct bacterial hemagglutination was investigated with 20 clinical isolates of Neisseria gonorrhoeae. The hemagglutination tests were performed by both a macrotechnique with glass slides and a microtechnique with autotrays. Only organisms from form type 1 or 2 colonies caused hemagglutination. There was no statistical difference at a 10% or higher level in hemagglutination powers of type 1 and type 2 organisms, of male urethral and female cervical isolates, and of the eight major human blood types (ABO-Rh). Of seven erythrocyte species tested, only human cells were agglutinated. D-Mannose did not prevent the agglutination. Rabbit antigonococcal serum and high-titer antigonococcal human sera inhibited the hemagglutination. The results suggest the pili are the mediators of hemagglutination and that their specific agglutination of human erythrocytes may be a correlate of their adherence to human mucosal cells in natural infection. Also, although the procedure is presently insensitive, it is possible to detect human antigonococcal antibody by inhibition of direct bacterial hemagglutination.